1994
DOI: 10.1002/j.1460-2075.1994.tb06712.x
|View full text |Cite
|
Sign up to set email alerts
|

A Salmonella protein that is required for resistance to antimicrobial peptides and transport of potassium.

Abstract: The ability of invading pathogens to proliferate within host tissues requires the capacity to resist the killing effects of a wide variety of host defense molecules. sap mutants of the facultative intracellular parasite Salmonella typhimurium exhibit hypersensitivity to antimicrobial peptides, cannot survive within macrophages in vitro and are attenuated for mouse virulence in vivo. We conducted a molecular genetic analysis of the sapG locus and showed that it encodes a product that is 99% identical to the NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 41 publications
1
102
0
1
Order By: Relevance
“…By transducing either the simple kdp-101::Mud1-8 insertion or the DUP*kdp-101::Mud1-8*nadA216 duplication into desired strains, it was possible to construct derivatives carrying the kdp-lacZ fusion in a kdp mutant or kdp ϩ background. Strain EG6602, which carries a Mud1-8 insertion in the sapG gene (the S. typhimurium homolog of trkA) (13), was obtained from E. Groisman. The sapG::Mud1-8 element in this strain was exchanged with the MudQ (Cm Lac Ϫ ) (20) element and transduced into the strains carrying the kdp-lacZ fusions to generate TrkA Ϫ (SapG Ϫ ) derivatives.…”
mentioning
confidence: 99%
“…By transducing either the simple kdp-101::Mud1-8 insertion or the DUP*kdp-101::Mud1-8*nadA216 duplication into desired strains, it was possible to construct derivatives carrying the kdp-lacZ fusion in a kdp mutant or kdp ϩ background. Strain EG6602, which carries a Mud1-8 insertion in the sapG gene (the S. typhimurium homolog of trkA) (13), was obtained from E. Groisman. The sapG::Mud1-8 element in this strain was exchanged with the MudQ (Cm Lac Ϫ ) (20) element and transduced into the strains carrying the kdp-lacZ fusions to generate TrkA Ϫ (SapG Ϫ ) derivatives.…”
mentioning
confidence: 99%
“…The sapABCDF operon encodes an ABC transporter system involved in resistance to antimicrobial peptides (Parra- Lopez et al, 1993). It has been proposed that the SapABCDF transporter system functions as a complex with SapG and SapJ to mediate both peptide and K + transport (Parra- Lopez et al, 1994). Finally, PgtE is a post-transcriptionally regulated component of the PhoQ/PhoP regulon with protease activity against alpha-helical cationic antimicrobial peptides .…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Genetic and biochemical evidence has demonstrated that gonococcal resistance to protegrin-1 and human cathelicidin LL-37 is modulated by overexpression of the mtr genes (Shafer et al, 1998). S. enterica mutants with a defect in the sap locus sharing homology with potassiumlinked efflux systems in E. coli are more susceptible to the cationic AMP protamine (Parra-Lopez et al, 1994), while a homologous locus in H. influenzae promotes resistance to β-defensin (Mason et al, 2005). Certain S. aureus strains harbor a multiresistance plasmid pSK1 that encodes the QacA efflux pump.…”
Section: Active Efflux Of Ampsmentioning
confidence: 99%
“…The PhoP/PhoQ regulatory system controls multiple virulence phenotypes in Salmonella spp., including a K + -coupled AMP efflux pump and the AMP protease, PgtE. S. enterica mutants in the PhoP/PhoQ regulatory system are more sensitive to AMP killing and significantly less virulent in the murine gastrointestinal infection model (Parra-Lopez et al, 1994). The inner membrane protein Mig-14 inhibits binding of CRAMP to Salmonella by an unknown mechanism (Brodsky et al, 2002).…”
Section: Antimicrobial Peptide Resistance Mechanisms Of Human Bacterimentioning
confidence: 99%
See 1 more Smart Citation